Coordination of hydraulic and morphological traits across dominant grasses in eastern Australia. (10th February 2023) - Griffin‐Nolan, Robert J.; Chieppa, Jeff; Knapp, Alan K.; Nielsen, Uffe N.; Tissue, David T.
Abstract: Leaf hydraulic traits characterize plant drought tolerance and responses to climate change. Yet, plant hydraulics are biased towards northern hemisphere woody species. We collected rhizomes of several perennial grass species along a precipitation gradient in eastern Australia and grew them in an experimental pot study to investigate potential trade‐offs between drought tolerance and plant morphology. We measured the following leaf hydraulic traits: the leaf water potential (Ψleaf ) at 50% and 88% loss of leaf hydraulic conductance (P50Kleaf and P88Kleaf ), the Ψleaf at 50% loss of stomatal conductance (P50gs ), leaf turgor loss point (TLP), leaf dry matter content (LDMC), leaf modulus of elasticity (ε), and the slope of the relationship between predawn and midday Ψleaf . We also measured basal area, tiller density, seed head density, root collar diameter, plant height, and aboveground biomass of each individual. As expected, grass species varied widely in leaf‐level drought tolerance, with loss of 88% hydraulic conductance occurring at a Ψleaf ranging from −1.52 to −4.01 MPa. However, all but one species lost leaf turgor, and most reached P50gs before this critical threshold. Taller more productive grass species tended to have drought vulnerable leaves characterized by low LDMC and less negative P88Kleaf . Species with greater tiller production experienced stomatal closure and lost turgor at more negative Ψleaf . Although our sample size was limited, we found no relationships between these species' traits and their climate of origin. Overall, we identified important hydraulic and morphological trade‐offs in Australian grasses that were surprisingly similar to those observed for woody plants: (1) xylem of taller species was less drought tolerant and (2) turgor loss occurs and stomatal closure begins before significant loss of Kleaf . These data build upon a small yet growing field of grass hydraulics and may be informative of species responses to further drought intensification in Australia. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.